The impacts of project uncertainty and relationship conflict on relationship continuity in construction: The role of political skill - Xiaoyan Huo; Shiya Gao; Huiyang Zhang (PLoS ONE, 2025)
Project uncertainty is a common feature in construction projects, and relationship conflicts often arise from interactions among project partners. This study examines the negative effects of project uncertainty and relationship conflict on relationship continuity, which is a key factor influencing collaboration and long-term mutual benefits in construction projects. While previous research has sufficiently addressed the role of formal mechanisms in promoting relationship continuity, this article emphasizes the importance of political skill as an effective soft mechanism. A moderated mediation model is proposed to investigate how political skill mitigates the negative impacts of project uncertainty and relationship conflict on relationship continuity. Data were collected through a structured questionnaire survey comprising 230 valid responses from 50 construction project teams, and hypotheses were tested using bootstrapping procedures. The results show that both project uncertainty and relationship conflict are negatively associated with relationship continuity. Furthermore, relationship conflict mediates the link between project uncertainty and relationship continuity, and this mediation effect is weakened when project partners demonstrate greater political skill. These findings underscore the value of political skill as a relationship management tool that can enhance the competitiveness of construction enterprises.